Cereal-legume cropping systems for enhanced productivity, food security, and resilience - Chikowo, Regis; Chirwa, Rowland; Snapp, Sieglinde S. (CAB International, 2022)
This chapter presents four approaches to the integration of legumes (such as soyabean, groundnut, and cowpea) in maize-dominated systems, through intercropping, efficient spatial arrangements, and legume-cereal sequences: (i) grain legume-maize rotations for increased yield stability on smallholder farms, (ii) 'doubled-up' legume technology for soil fertility maintenance and human nutrition, (iii) innovative maize-common bean (*Phaseolus vulgaris*) intercropping and fertilizer application for improved productivity, (iv) targeted cropping sequences (rotations adapted to farm size limitations and farmer goals) and associated elements for sustainable intensification on small farms. The first three technologies are based specifically on legumes that smallholder farmers can introduce to increase the productivity of their farms. The fourth demonstrates how different legume-based technologies can be integrated on farms with different resources, allowing farmers to diversify and intensify their production in a sustainable manner.